An innovation diffusion perspective of e-consumers’ initial adoption of self-collection service via automated parcel station - Wang, Xueqin (2018)
Purpose - As an application of Self-Service Technology (SST), Automated Parcel Station (APS) is emerging as a logistics innovation to address the inefficiency and delivery failure in conventional home delivery. However, the long term viability of APS depends on consumers’ acceptance of such concept. In response, a behavioural study on consumers’ adoption of self-collection service via APS is conducted. Design/methodology/approach - By synthesising theoretical insights from innovation diffusion literature and attitude theories, a conceptual model is developed and empirically validated. Perceived characteristics of APS are present to directly influence consumers’ adoption intention, or indirectly through attitude. A total of 170 valid responses are collected from a survey conducted in Singapore and the data are analysed using Structural Equation Modelling (SEM). Findings – Consumers’ favourable attitude and perceived relative advantage of APS directly lead to stronger adoption intention. On the contrary, consumers’ perceptions on compatibility and trialability and on complexity indirectly influence their adoption intention via attitude, in a positive and in a negative way respectively. Additionally, attitude is found to be the most influential factor contributing to consumers’ adoption intention. Research limitations/implications - The scope of this paper is limited to e-consumers’ initial adoption decision. Future research should examine consumers’ adoption behaviour further down the innovation adoption process, such as continuance and commitment. Originality/value - This research conceptualises and validates consumers’ adoption behaviour of APS from a synthesised view of innovation diffusion and attitude theories, theoretically and empirically contributing to the field of study on logistics innovations from consumers’ perspective.